Age-Dependent Differences in Systemic and Cell-Autonomous Immunity to L. monocytogenes - Ashley M. Sherrid; Tobias R. Kollmann (Clinical and Developmental Immunology)
Host defense against infection can broadly be categorized into systemic immunity and cell-autonomous immunity. Systemic immunity is crucial for all multicellular organisms, increasing in importance with increasing cellular complexity of the host. The systemic immune response to Listeria monocytogenes has been studied extensively in murine models; however, the clinical applicability of these findings to the human newborn remains incompletely understood. Furthermore, the ability to control infection at the level of an individual cell, known as “cell-autonomous immunity,” appears most relevant following infection with L. monocytogenes; as the main target, the monocyte is centrally important to innate as well as adaptive systemic immunity to listeriosis. We thus suggest that the overall increased risk to suffer and die from L. monocytogenes infection in the newborn period is a direct consequence of age-dependent differences in cell-autonomous immunity of the monocyte to L. monocytogenes. We here review what is known about age-dependent differences in systemic innate and adaptive as well as cell-autonomous immunity to infection with Listeria monocytogenes.